Konflik Orang Tua Dan Anak Pada Novel Patah Hati terindah Karya Aguk Irawan - Pandika Adi Pratama; Riphal Zulfikar Akiko Takada Z; Eva Dwi Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
This research discusses the conflict between parents and children that occurs in the novel Patah Hati Terindah by Aguk Irawan. The purpose of this research is to look at the conflict that occurred between Hamdan and his parents. Hamdan's birth, which his parents did not expect, was the initial trigger for the conflict between him and his parents. The research method used this time is descriptive qualitative with a hermeneutical approach. The technique used is a close and read technique, namely reading the entire novel. The results of this research show that there is family conflict in the novel Patah Hati Terindah by Aguk Irawan. This conflict occurs in the form of speech and action.